Libraries, Digital Culture and Sustainable Development: The Synergy of Knowledge and Technology - Lomachinskiy, Bogdan; Yang, Qi; Khrypko, Svitlana; Binkivska, Kristina; Yakovenko, Olena; Patlaichuk, Oksana; Stupak, Olga; Ishchuk, Alla (European Journal of Sustainable Development, 2025)
This article explores the integration of digital culture technologies into library operations in the context of advancing the goals of sustainable development. It emphasizes that, in the digital era, libraries are no longer merely repositories of books — they are evolving into digital and educational hubs aimed at bridging the digital divide in society. This transformation calls for a deeper understanding of how digital culture is reshaping the roles and functions of libraries. Digital technologies enable libraries to ensure equitable access to knowledge, aligning with the Sustainable Development Goals (SDGs). The fusion of traditional and digital library services opens new avenues for educational innovation, cultural heritage preservation, scientific advancement and communication. The adoption of digital culture in library practices fosters the democratization of knowledge through open access to books, scholarly research and archives. Developing digital competencies among both librarians and users helps to reduce information inequality and enhances information security. The presence of digital culture in library activities is also transforming models of information consumption — traditional reading is increasingly complemented by multimedia content, virtual reality, interactive learning platforms, creating virtual spaces for dialogue, learning and collaboration. The article also highlights the importance of the environmental dimensions of digital transformation in libraries, noting that libraries can play a vital role in promoting ecological awareness and adopting "green" technologies in information resource management. Keywords: digital culture, sustainable development, libraries, library digitalization, digital technologies, information literacy, intercultural communication, digital competencies, digital library services